Institutional Role of Farmers Apples in Pasuruan - Murtadlo, Kholid (International Journal of Psychosocial Rehabilitation, 2020)
This study purpose to understand the socioeconomic institutional apple growers in Pasuruan, East Java, Indonesia. The first phase of the study used a qualitative method with a phenomenology approach. The results showed that the phenomenon of institutional apple growers in Pasuruan developed system of togetherness and traditional by making agreements rules on farmers who have in common the ability to cultivate apples, the capabilities of these farmers gained from the experience of parents and fellow apple growers, experience emulated the success of fellow farmers to apply to its apple farm in the hope of increasing his apple crop, to meet the basic needs of the family and their environment as well as additional income to meet the needs of others. The conclusion of this study is local institutions that are informal in the informal internalized in running a deal could accelerate the socio-economic development of farmers Apples.